PENERAPAN PERMAINAN TRADISIONAL LOMPAT TALI BERVARIASI UNTUK MENINGKATKAN PERCAYA DIRI DAN MOTORIK KASAR ANAK USIA DINI DI TK DHARMA WANITA TAIS PADA KELOMPOK B - Zelmi Sulastri (DIADIK, 2023)
This study aims to describe the application of the method of playing through jumping rope games to increase self-confidence and gross motor skills of early childhood in group B at Dharma Wanita Tais Kindergarten; (2) Describe and analyze the effectiveness of the application of the playing method through the game of jumping rope to improve the gross motor skills of early childhood in group B at Dharma Wanita Tais Kindergarten. This type of research uses a combination of Classroom Action Research (CAR) with quasi-experimental, which is an observation of learning activities in the form of an action, which is deliberately raised that occurs in a class together. Subject of this research are B1 for CAR group, B2 for experiment group and B3 for control group. The tool used in data collection is an observation sheet. The results of classroom action research (CAR) show that there is an increase in children's self-confidence and gross motor skills in each cycle. This can be seen from the increase in every aspect of self-assessment and gross motor skills. The implication of this research is that teachers can try to apply various traditional jumping rope games as a daily learning method. The results of this study recommend that teachers can prefer learning models and methods as well as learning media that can improve aspects of child development.